Genre, couple et violence dans Love me tender de Jean-Hugues Mirédin - Karine Bénac-Giroux (Amnis)
In his play, Love me tender created in 2017, Jean-Hugues Mirédin summons both parody, humour and stereotypes, as well as the questioning of phenotypes and representations of gendered identities. The play questions gendered symbolic constructions within scenic images and work on imaginary bodies that suggest an omnipresent violence and tension at the heart of gender relations. If virility becomes burlesque here, the link remains strong between the eroticization of the female body and the violence of sexual desire, while the couple finally appears as a pure game of signifiers.